N-type calcium current, Cav2.2, is enhanced in small diameter sensory neurons isolated from Nf1+/− mice - Duan, J-H. (2014)
Major aspects of neuronal function are regulated by Ca(2+) including neurotransmitter release, excitability, developmental plasticity, and gene expression. We reported previously that sensory neurons isolated from a mouse model with a heterozygous mutation of the Nf1 gene (Nf1+/−) exhibited both greater excitability and evoked release of neuropeptides compared to wildtype mice. Furthermore, augmented voltage-dependent sodium currents but not potassium currents contribute to the enhanced excitability. To determine the mechanisms giving rise to the enhanced release of substance P and calcitonin gene-related peptide in the Nf1+/− sensory neurons, the potential differences in the total voltage-dependent calcium current (I(Ca)) as well as the contributions of individual Ca(2+) channel subtypes were assessed. Whole-cell patch-clamp recordings from small diameter capsaicin-sensitive sensory neurons demonstrated that the average peak I(Ca) densities were not different between the two genotypes. However, by using selective blockers of channel subtypes, the current density of N-type (Cav2.2) I(Ca) was significantly larger in Nf1+/− neurons compared to wildtype neurons. In contrast, there were no significant differences in L-, P/Q- and R-type currents between the two genotypes. Quantitative real-time PCR measurements made from the isolated but intact dorsal root ganglia indicated that N-type (Cav2.2) and P/Q-type (Cav2.1) Ca(2+) channels exhibited the highest mRNA expression levels although there were no significant differences in the levels of mRNA expression between the genotypes. These results suggest that the augmented N-type (Cav2.2) I(Ca) observed in the Nf1+/− sensory neurons does not result from genomic differences but may reflect post-translational or some other non-genomic modifications. Thus, our results demonstrate that sensory neurons from Nf1+/− mice, exhibit increased N-type I(Ca) and likely account for the increased release of substance P and calcitonin gene-related peptide that occurs in Nf1+/− sensory neurons.